Role Of Urban Farmer Group's Leader As Opinion Leader On Utilizing Urban Yard In Yogyakarta City - Rachman Agatha Zenobia (EDP Sciences, 2021)
One of urban agriculture activities in Yogyakarta City was utilizing yard through farmer groups coordinated by group‟s leader as opinion leader. This study aims to i) Describe farmer group's activities and management on utilizing urban-yard in Yogyakarta City, ii) Determine role of group's leader in utilizing urban-yard in Yogyakarta City, iii) Analyze factors related to member‟s perceptions of the role of group‟s leader in utilizing urban-yard in Yogyakarta City. There were 48 samples selected by multistage random sampling. Data were analyzed by descriptive analysis to describe activities and management of farmer groups, table analysis to determine role of group‟s leader, and rank spearman correlation analysis to analyze factors related to member‟s perceptions of role of group‟s leader. The result indicated that urban farmer group had several activities. On management, urban farmer groups didn‟t have comprehensive organizational structure and administrative records. The instructive, consultative, and participatory roles of group‟s leader can be categorized very good. Meanwhile liaison role was categorized good. Factor that had significant correlation to member‟s perceptions of the role of group‟s leader was role of agricultural extention.